Survival-Span Method: How to Qualitatively Estimate Lifespan to Improve the Study of Aging, and not Disease, in Aging Studies - Adelöf, Julia; Ross, Jaime M.; Zetterberg, Madeleine; Hernebring, Malin (Frontiers in Aging, 2021)
Lifespan analyses are important for advancing our understanding of the aging process. There are two major issues in performing lifespan studies: i) late-stage animal lifespan analysis may include animals with non-terminal, yet advanced illnesses, which can pronounce indirect processes of aging rather than the aging process per se and ii) it often involves challenging welfare considerations. Herein, we present an option to the traditional way of performing lifespan studies by using a novel method that generates high-quality data and allows for the inclusion of excluded animals, even animals removed at early signs of disease. This Survival-span method is designed to be feasibly done with simple means by any researcher and strives to improve the quality of aging studies and increase animal welfare.